Correlation Between Coronavirus Disease 2019 Severity and Noninvasive Assessment of Liver Fibrosis in Patients with Metabolic Dysfunction-Associated Fatty Liver Disease - Tungtrongchitr, Nuttapat; Srivanitchapoom, Nantaporn; Hirunpat, Pornrujee; Sungkanuparph, Somnuek (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Metabolic dysfunction-associated fatty liver disease is a crucial global health concern. Studies have shown that metabolic dysfunction-associated fatty liver disease patients are at higher risk of severe coronavirus disease 2019. However, there are no precise measures of the correlation between the degree of metabolic dysfunction-associated fatty liver disease fibrosis and coronavirus disease 2019 severity. This study evaluated the association between metabolic dysfunction-associated fatty liver disease with varying degrees of fibrosis and coronavirus disease 2019 prognosis. Materials and Methods: All hospitalized coronavirus disease 2019 patients who had liver steatosis as determined by computed tomography scan were included. Metabolic dysfunction-associated fatty liver disease was diagnosed in accordance with international consensus criteria. Liver fibrosis was assessed using the nonalcoholic fatty liver disease fibrosis score, FIB-4 and FIB-8 indexes. Coronavirus disease 2019 severity was defined using World Health Organization criteria. Logistic regression was used to determine the associations between varying degrees of fibrosis and the severity of coronavirus disease 2019. Results: A total of 996 confirmed hospitalized coronavirus disease 2019 cases with complete data were reviewed; of these, 296 (29.7%) cases of metabolic dysfunction-associated fatty liver disease were diagnosed. Metabolic dysfunction-associated fatty liver disease patients with any fibrotic state had more severe coronavirus disease 2019 than nonmetabolic dysfunction-associated fatty liver disease patients (adjusted odds ratio 1.912, 95% CI 1.363-2.684; P < .05). Multiple logistic regression analysis showed that metabolic dysfunction-associated fatty liver disease patients with significant fibrosis according to the FIB-8 score were more likely to have severe coronavirus disease 2019 (adjusted odds ratio 5.458, 95% CI 1.481-20.110; P < .05). Conclusion: The presence of metabolic dysfunction-associated fatty liver disease in hospitalized coronavirus disease 2019 patients strongly correlated with the severity of coronavirus disease 2019. The hepatic FIB-8 index appears to provide the best prognostic value among the fibrosis scores in metabolic dysfunction-associated fatty liver disease patients with coronavirus disease 2019.